ORGANIZATION MANAGEMENT STRUCTURE - Mirkhaydarov Ismoil Mirkhoshim ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The essence of the article is that it expresses an opinion about the management structure, which has a material and technical base and manages certain management tasks. According to him, the importance of management in the development of the organization, its role and functions are discussed. Also, successful management factors are analyzed one by one.